Liquid detergent from palm oil and palm kernel oil - Nurul Ika Amira, Zakaria (2015)
Manufacturing of detergent from distilled fatty acids of palm kernel oil (PKO) and palm oil (PO) is a well-established technology in Malaysia. In this research, the production of detergent from palm kernel oil is by direct saponification fats and oils and is evaluated for water hardness, pH value, viscosity and foam ability of liquid detergent .The objective of this research is to study the production of liquid detergent from palm kernel oil (PKO) and palm oil (PO). This is because of palm oil (PO) and palm kernel oil (PKO) as raw material have important fatty acids involved in detergent making which are C16-C18 and C12-C14 which contribute to the detergency properties, lathering and washing properties of the soaps. Parameters that involve in this research are ratios concentration of raw materials, quantity of water and speed. For the concentration, the ratio is from 0 until 100 %, for the quantity of water the best range is from 200 mL to 1000mL until get the required texture of liquid detergent, for the speed the best range is from 600- 1500 rpm, and within constant the time of process which is 30 minute. The optimum concentration in manufacturing of soap is making from a blend of 70% PO and 30% PKO with the speed minimum 1500 rpm at room temperature. The result is done and the best ratio is 70% PO and 30 % PO with minimum 400 mL water and minimum 1500 rpm speed. This ratio gave a good texture of detergent and can save cost of manufacturing because of using mixture of 70% PO and 30% PKO.